Factors Affecting International Price Policy in Algerian Small and Medium-Sized Exporting Companies - ركيمة, فارس; لعبني, عمر (Finance and Business Economies Review, 2021)
We have tried, through this study, to shed light on the impact of different elements of the international marketing environment on the implementation of pricing strategies in small and medium-sized Algerian companies that have an export activity. In order to better understand the different dimensions of the study, the statistical program Spss version 22 was used to determine how the independent variable affects the dependent variable. This research concluded with a set of results, the most important of which is the presence of a low impact, with statistical significance, of the elements of the marketing environment on the price policy of small and medium-sized exporting companies. Based on the above, a set of recommendations has been proposed, most of which affirm the need to place greater emphasis on studying and analyzing the elements of the international marketing environment in order to achieve a successful pricing policy.